Assessment of Hospitalised Patient Satisfaction with Nursing Care in the Gynaecology and Obstetrics Department of Benghazi Medical Center, Libya - Omar, Fatma Abdalla Atitalla; Mustafa, Fathi Saad; Elamrony, Randa Mahmoud Gadalla (Journal of medical and pharmaceutical sciences, 2023)
Satisfaction with nursing care is believed to be an indicator of the quality of the health setting, for this reason, many stakeholders and managers focus on measuring patients’ satisfaction to gather crucial information that could improve nursing service quality. The purpose of this study was to assess patients’ satisfaction with nursing care in the gynaecology and obstetrics department at Benghazi Medical Center (BMC) in Libya. Method: This study utilized a cross-sectional survey design. The survey was conducted from April to May 2022. Participants: - The population of the study consisted of adult patients who agreed to participate in the research and met the inclusion criteria, A convenient sampling method was applied in this study (n=300). Instrument: The data were collected through patient satisfaction with the nursing care quality questionnaire (PSNCQQ). The first section collected general information and demographic data; the second section consisted of a questionnaire related to patient satisfaction with nursing care. The scale included additional questions designed to assess satisfaction with the overall quality of care and treatment received during hospitalization, the overall quality of nursing care, and the likelihood that the patient would recommend the hospital to relatives and friends. The findings: The patients rated their satisfaction with nursing care as being at a low level of satisfaction. Moreover, patients reported less satisfaction with the overall quality of care and services received during their hospital stay and reported that they would not recommend this hospital to their families and friends. Recommendation: Periodic assessments to measure patients’ satisfaction levels with nursing care in different units and locations, and with a larger sample, could help healthcare facilities to guarantee the provision of high-quality patient care. - The results of the evaluation should be used to develop potential new strategies to improve the level of nursing services in the hospital.
Keywords: Patient Satisfaction; Nursing Care; Health Care Quality Assessment; gynecology and obstetrics department